2018
DOI: 10.1016/j.ekir.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Short Leukocyte Telomere Length Predicts Albuminuria Progression in Individuals With Type 2 Diabetes

Abstract: IntroductionTelomere length, a marker for biological aging, is implicated with diabetic kidney disease (DKD); however, the association between telomere length and albuminuria progression among Asian patients with type 2 diabetes (T2D) is not well understood. Here, we aim to study whether leukocyte telomere length (LTL) may independently predict albuminuria progression in patients with T2D with preserved renal filtration function (estimated GFR >60 ml/min per 1.73 m2 and urine albumin-to-creatinine ratio [uACR]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 56 publications
(68 reference statements)
0
29
0
Order By: Relevance
“…Furthermore, the stronger association of changes in VFA and LTL dynamics than in BMI and LTL, strengthens the link between central obesity and telomere biology. Although we do not have data to infer a relationship between ethnic disparities in obesity‐dependent LTL attrition and susceptibility to diabetes complications, we had previously found that T2D individuals with shorter LTL are at increased risk for albuminuria progression . We postulate that in different ethnicities, LTL attrition driven by changes in adiposity may be weighted differently (ie, mediated by adiposity to a greater degree among Chinese, but less so among Malays and Indians).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Furthermore, the stronger association of changes in VFA and LTL dynamics than in BMI and LTL, strengthens the link between central obesity and telomere biology. Although we do not have data to infer a relationship between ethnic disparities in obesity‐dependent LTL attrition and susceptibility to diabetes complications, we had previously found that T2D individuals with shorter LTL are at increased risk for albuminuria progression . We postulate that in different ethnicities, LTL attrition driven by changes in adiposity may be weighted differently (ie, mediated by adiposity to a greater degree among Chinese, but less so among Malays and Indians).…”
Section: Discussionmentioning
confidence: 89%
“…Although we do not have data to infer a relationship between ethnic disparities in obesitydependent LTL attrition and susceptibility to diabetes complications, we had previously found that T2D individuals with shorter LTL are at increased risk for albuminuria progression. 21 We postulate that in different ethnicities, LTL attrition driven by changes in adiposity may be weighted differently (ie, mediated by adiposity to a greater degree among Chinese, but less so among Malays and Indians). Whether changes in telomere dynamics explain the ethnic disparities in diabetes complications and mortality in the multiethnic Singapore population warrants further investigation.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Furthermore, acute myocardial infarction and reperfusion accelerate immunosenescence in cytomegalovirus-seropositive patients [ 100 ]. LTL attrition also associates with obesity [ 101 , 102 ] and with the presence and number of diabetic complications in type 2 diabetes patients [ 103 , 104 , 105 , 106 , 107 , 108 , 109 ]. It has been recently shown that reducing obesity may reduce the risk of diabetes complications associated with shorter LTL, at least in some Chinese population [ 110 ].…”
Section: Telomere Length In Age-associated Diseasesmentioning
confidence: 99%